Classroom Interaction: Teacher Talk and Students' Responses - Handayani, Gayatri Mayang; Cahyono, Arik Fajar (Icon: Islamic Communication and Contemporary Media Studies, 2024)
Many of Primary schools in Banyuwangi don’t have adequate number of English teachers, so they prefer to give English subject by classroom teachers. Regarding this, classroom teachers don’t have educational English background. It affected the learning process in classroom, especially classroom interaction. The study was conducted to find out the types of teacher talk produced during classroom interaction and students’ responses toward it.  The method used in this research is descriptive case study.  The results of the study were the most type that frequently produced by the teacher was giving information (21.7%) in direct influence and praising or encouraging (15%) in indirect influence.  Then, the results of students’ responses, it showed that 6 out of 10 types of teacher talk could be responded well by the students.  Hopefully, these results would give a great contribution to the enrichment of the classroom interaction by teacher talk and students’ responses.